Carbon-supported binary transition metal chalcogenide used as cathode catalyst for oxygen reduction in microbial fuel cell. (18th May 2017) - Pu, Liangtao; Liu, Di; Li, Kexun; Wang, Junjie; Yang, Tingting; Ge, Baochao; Liu, Ziqi
Abstract: This study investigates the application of carbon-supported inverse spinel binary transition metal chalcogenide as the catalyst for oxygen reduction reaction (ORR) in air-cathode microbial fuel cell (MFC). The obtained maximum power density (MPD) is 2000 ± 59 mW m −2, 2.25 times as high as the bare activated carbon (AC) (888 ± 56 mW m −2 ). Total resistance of the modified MFC was decreased evidently, and the kinetics activity toward ORR was promoted significantly and rotating disk electrode results show that catalyst electrocatalytic activity for ORR through four-electron reaction pathway. X-ray photoelectron spectroscopy and Brunauer–Emmett–Teller results indicate that NiCo2 S4 /AC contains more octahedral catalytic active sites of Co 3+ and micropores than NiCo2 O4 /AC. S atom is successfully incorporated into AC and shows more benefit than oxygen atom. All findings suggest that the synthetic composite can be a potential cathode catalyst for ORR in MFC. Highlights: AC-supported inverse spinel chalcogenide was used as effective air-cathode catalyst. The obtained MPD was 2000 ± 59 mW/m 2, 2.25 times as high as the bare AC. NiCo2 S4 /AC proceeded via the most efficient four-electron process. NiCo2 S4 /AC contained catalytic active sites of Co 3+, having good kinetics activity. S incorporated into AC and more micropores made NiCo2 S4 /AC more active for ORR.